1, 3‐Diazasilabicyclo[1.1.0]butane with a Long Bridging N−N Bond. Issue 11 (8th February 2016) - Xiao, Xu‐Qiong; Dong, Zhaowen; Li, Zhifang; Yan, Chenting; Lai, Guoqiao; Kira, Mitsuo
Abstract: A 1, 3‐diazasilabicyclo[1.1.0]butane (1 ) is synthesized as thermally stable crystals by using the cycloaddition reaction of an isolable dialkylsilylene with aziadamantane. The bridge N−N bond length of1 (1.70 Å) is the longest among those of known N−N singly‐bonded compounds, including side‐on bridged transition‐metal dinitrogen complexes. The compound1 is intact in air but moisture sensitive. No reaction occurs with hydrogen, even under pressure at 0.5 MPa. Irradiation of1 with light gives an isomer quantitatively by N−N and adamantyl C−C bond cleavage. The origin of the remarkable N−N bond elongation is ascribed to significant interaction between a Si−C σ* and Ν−Ν π and σ orbitals as determined by DFT calculations of model compounds. Abstract : Come a long way : A 1, 3‐diazasilabicyclo[1.1.0]butane was synthesized and features the longest N−N bond (1.70 Å) among known N−N singly‐bonded compounds. The compound is intact in air but moisture sensitive, and no reaction occurs with hydrogen, even under pressure at 0.5 MPa. The origin of the N−N bond elongation is ascribed to significant interaction between a Si−C σ* orbital and Ν−Ν π and σ orbitals.